Bearish mood on world commodity markets - Heinz Kolbe (Intereconomics, 1982)
For two years now the international raw materials markets have been characterised by a lasting slump. The weak and short-lived reactions to the Falklands crisis and to the intensification of hostilities between Israel and its Arab neighbours are indicative of the situation. During this year's summer months prices on markets for industrial raw materials and food and tropical beverages hit their lowest level since spring 1978. What are the prospects for the development of raw materials prices?
Keywords: 330; Economic Trends